2020
DOI: 10.3390/children7120311
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception of COVID-19 Infection and Adherence to Preventive Measures among Adolescents and Young Adults

Abstract: To explore factors influencing adolescents and young adults’ (AYAs) risk perception of COVID-19 and adherence to public health measures, we conducted a cross-sectional online survey of AYAs (14–22 years old) from Quebec (Canada) recruited through school and community partners in April 2020 during the first wave of the COVID-19 pandemic. The study included 3037 participants (mean age = 17.7 years, 74.6% female). AYAs had higher mean (standard deviation (SD)) risk perception of COVID-19 for their relatives (8.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
84
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 33 publications
(42 reference statements)
21
84
1
4
Order By: Relevance
“…They argued that adolescents may have been more motivated to engage in protective behaviors if they were reminded about the possible consequences of infection for people in high-risk groups, such as older people [ 20 ]. Yang et al [ 21 ] came to the same conclusion, and found that protecting family and friends at risk was a motivating factor for adolescents to adhere to preventive measures.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…They argued that adolescents may have been more motivated to engage in protective behaviors if they were reminded about the possible consequences of infection for people in high-risk groups, such as older people [ 20 ]. Yang et al [ 21 ] came to the same conclusion, and found that protecting family and friends at risk was a motivating factor for adolescents to adhere to preventive measures.…”
Section: Introductionmentioning
confidence: 81%
“…Most adolescents do not develop severe symptoms when infected with Covid-19 [ 19 ], which might make then less inclined to seek out information due to a lower perceived risk [ 20 ]. One study found that higher perceived risk among adolescents was associated with the presence of risk factors for and knowledge of Covid-19, and that knowledge was related to better compliance with preventive measures [ 21 ], suggesting that improving knowledge about Covid-19 could be a good strategy to increase protective behavior in this age group [ 21 ]. Abbott et al [ 20 ] criticized messaging efforts aimed at adolescents in the USA, which stressed that it is unlikely the virus would make them seriously ill.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study on adolescents with chronic diseases, including asthma, 60% respondents reported high adherence to preventive measures such as hand-washing, avoiding group gatherings, reducing use of public transportation and avoiding public places. The rate of adherence to preventive measures was similar for respondents with and without chronic diseases ( 42 ). However, evidence on young children is lacking.…”
Section: Discussionmentioning
confidence: 98%
“…However, the population in their study was medical students who have higher health literacy than the samples studied in the present study. Regarding the knowledge and understanding of the disease in a study in Canada, the results showed that the knowledge and understanding of the risk of the disease are effective in observing the preventive behaviors for COVID-19 [ 42 ]. In the studies of Smith et al, 2020, in the United Kingdom and Carlucci et al, 2020, in Italy, low perception of risk played a role in non-adherence to home quarantine and health norms [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%